Gmachy terytorialnych władz wojskowych szczebla okręgowego Wojska Polskiego w Łodzi - Jarno, Witold; Waingertner, Przemysław (Przegląd Nauk Historycznych, 2015)
Łódź, though doesn’t play a great role in administrative and territorial structure of today's Polish Army, however, has a long and rich history in this respect. The city was the seat of the military authorities of the district-level territorial both in the Interwar Poland, as well as the People’s Republic of Poland. During the second Republic of Poland they were located at Spacerowa Street 4, renamed soon on Tadeusz Kościuszko Street 4 (later at T. Kościuszko Street 67, finally at Konstantynowska Street 81/83 – now The Legions’ Street). The individual cells of the military authorities also were located for example at Piotrkowska Street, Stanislaw Moniuszko Street and Zachodnia Street. Invasion of Poland of 1939 and the fall of the Second Republic of Poland marked the liquidation of Poland and Polish military structures in the city. Their headquarters were taken over by the Germans. Again in the role of the headquarters of the military authorities of the district level, Łódź is revived in 1945. After 1989 the role of Łódź in the territorial structure of the army began to systematically degrade, and military buildings and facilities have passed into the hands of the city, or private.